Blind spots : why product development projects miss their targets - Streit, Paul (Business Expert Press, 2025)
Why do so many new products fail in the market?What causes schedule and cost overruns?How can products be developed right the first time?Unlike books focused solely on speeding development or cutting costs, Blind Spots: Why Product Development Projects Miss Their Targets reveals the often-overlooked traps that lead to costly failures and...